3D printing of patient-specific anatomy: A tool to improve patient consent and enhance imaging interpretation by trainees. (3rd September 2015) - Liew, Yaoren; Beveridge, Erin; Demetriades, Andreas K.; Hughes, Mark A.
Abstract : We report the use of three-dimensional or 3D printed, patient-specific anatomy as a tool to improve informed patient consent and patient understanding in a case of posterior lumbar fixation. Next, we discuss its utility as an educational tool to enhance imaging interpretation by neurosurgery trainees.